Cultural roots of Kongo prophetism - MacGaffey, Wyatt (History of Religions, 1977)
The paper explores a systematic way of comparing Kimbanguism in modern Zaire (Congo), with Antonism, a religious movement that occurred among the same BaKongo people in 1704. The structure of Kongo religion is seen as a set of roles ("commissions") derived from indigenous cosmology and assumptions about power. It is shown that Antonine and Kimbanguist prophets both conform to the role of priest of a local spirit (simbi), one who uses healing powers in the public interest. The conversion of the Kono King in 1491 was a movement of the same sort, and in later centuries Capuchin missionaries themselves unwittingly played the role of simbi priest.
Keywords: Africa; West – Religion; Congo (Democratic Republic) – Religion; Kimbanguism; Peer reviewed